Gaspar de Jovellanos' Critique of Bullfighting. Issue 11 (12th November 2020) - Andrade, Gabriel
Abstract: Bullfighting debates in Spain are increasingly intense. Defenders of bullfighting as sport and as art, typically argue that many of the country's most esteemed intellectual and artistic figures were bullfight enthusiasts. This is admittedly true, but by the same token Spain has a long tradition of anti-bullfighting thought. One prominent critic of bullfighting in the eighteenth century was Gaspar Melchor Jovellanos. Often considered the best representative of the Spanish Enlightenment, Jovellanos did not address bullfighting as a central concern. But, in some writings, he did level important criticisms against this sort of spectacle. Defenders of bullfighting frequently argue that Jovellanos' critique of bullfighting relies mostly on economic arguments. While it is true that Jovellanos offered economic reasons to oppose bullfighting, a closer reading of his works reveals that he had a larger concern with the violent nature of bullfighting, which cohered with his Enlightenment philosophy.